KEGIATAN EMPLOYEE RELATIONS DALAM SITUASI PANDEMI COVID-19 - Deby Astarina; Guntur F. Prisanto (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this research is to find out the activity performd by non-essential company in optimizing employee relations activities and employee’s anxiety that arises during the Covid-19 pandemic focusing on internal communication. Using descriptive qualitative method and qualitative approaches, this research outlines a descriptions of the conditions and obstacles of the employee relations during Covid-19 pandemic, at PT. Hidayah Insan Mulia obtained through in-depth interview with employee and Human Resources division. The outcomes of this research indicates that although the company cannot carry out the employee relations activities as in normal condition and has to do some efficiency, but the company keep paying attention to the health and safety of their employees, with focusing on the treatment and recovery of employees who are confirmed positive for Covid-19. In this case, the company implements an open and kinship communication system through technique of communication performed directly by management (leader) and Human Resources division as Communication Facilitator, so that there is mutual understanding in internal communication between employees and management regarding the difficult situation experienced by the company. The application of online media as a communication medium is also well utilized by the company, so that communication can run well even though there are many uncertain conditions experienced and felt by employees, especially issues related to the continuity of the employee’s tenure. The internal communication performed by the company in employee relations activities is quite optimal. That causes many employees remain stay with the company in the face of the pandemic.